Quality attribute of plantain (Musa paradisiaca) sponge-cake supplemented with watermelon (Citrullus lanatus) rind flour - Adegunwa, M.O.; Oloyede, I.O.; Adebanjo, L.A.; Alamu, Emmanuel Oladeji (Informa UK Limited, 2019)
his study is aimed at supplementing Watermelon rind flour (WF) into cakes production with Plantain Flour (PF). Six cake samples were produced from the composite mixture of PF and WF in varying proportions of 100:0, 90:10, 80:20,70:30, 60:40 and 50:50. The composite flour of plantain-watermelon rind was evaluated for proximate, functional and pasting properties while the cakes were assessed for proximate, texture and sensory qualities using laboratory standard methods. The water absorption capacity (WAC) of the composite flours has a significant (P < 0.05) increase as the volume of WF increases from 0 to 50%. Cake produced from PF substituted with 50% WF has the highest value of protein (10.58%). The substitution of 10% of WF showed the highest score rating by the panelist in overall acceptability (7.60). This study has provided the recipe for the formulation of quality cake with PF and WF that could be acceptable by consumers.